2013
DOI: 10.1371/journal.pone.0064696
|View full text |Cite
|
Sign up to set email alerts
|

Urinary ATP May Be a Dynamic Biomarker of Detrusor Overactivity in Women with Overactive Bladder Syndrome

Abstract: BackgroundNowadays, there is a considerable bulk of evidence showing that ATP has a prominent role in the regulation of human urinary bladder function and in the pathophysiology of detrusor overactivity. ATP mediates nonadrenergic-noncholinergic detrusor contractions in overactive bladders. In vitro studies have demonstrated that uroepithelial cells and cholinergic nerves from overactive human bladder samples (OAB) release more ATP than controls. Here, we compared the urinary ATP concentration in samples colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 37 publications
4
66
0
Order By: Relevance
“…According to Gorman et al (2007), human plasma ATP concentrations range from 1 mM in healthy individuals to as low as 28 nM. Silva-Ramos et al (2013) recorded levels of urinary ATP in the range of 2-6 nM for healthy patients and 7-11 nM for patients with overactive bladder syndrome. Jin et al (2004) found ATP concentrations ranging from 2.5 to 32 nM in oral Candida albicans biofilms.…”
Section: Biosensor Fabrication and Performance Characterizationmentioning
confidence: 99%
“…According to Gorman et al (2007), human plasma ATP concentrations range from 1 mM in healthy individuals to as low as 28 nM. Silva-Ramos et al (2013) recorded levels of urinary ATP in the range of 2-6 nM for healthy patients and 7-11 nM for patients with overactive bladder syndrome. Jin et al (2004) found ATP concentrations ranging from 2.5 to 32 nM in oral Candida albicans biofilms.…”
Section: Biosensor Fabrication and Performance Characterizationmentioning
confidence: 99%
“…Increased levels of urinary ATP have been demonstrated in patients with interstitial cystitis 133 , OAB 134 , and other functional disorders of the urinary bladder 95 . Primary bladder urothelial cells taken from these patients also exhibit increased ATP release in response to mechanical stretch 133 , hypotonic stress 135 , or electrical field stimulation 136 .…”
Section: Roles In Urinary Bladder Dysfunctionmentioning
confidence: 99%
“…In recent papers it was reported that women with OAB have high urinary levels of ATP compared to controls and the nucleotide levels increase with water intake and it was suggested therefore that higher urinary ATP may be a useful prognostic marker for detrusor overactivity [142,615]. It was suggested that the increased concentrations of ATP in the urine is probably due to enhanced ATP release from proliferating urothelium and that decreased ATP metabolism may also contribute to the high urine levels of ATP [615].…”
Section: Healthy Bladdermentioning
confidence: 99%
“…It was suggested that the increased concentrations of ATP in the urine is probably due to enhanced ATP release from proliferating urothelium and that decreased ATP metabolism may also contribute to the high urine levels of ATP [615]. The ATP concentration in urine was inversely related to the volume at the first desire to void in women patients with OAB [142].…”
Section: Healthy Bladdermentioning
confidence: 99%